2010
DOI: 10.1111/j.1469-8749.2010.03635.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of kinematic measures of functional reaching in children with cerebral palsy

Abstract: AIM The determination of rehabilitation effectiveness in children with cerebral palsy (CP) depends on the metric properties of the outcome measure. We evaluated the reliability of kinematic measures of functional upper limb reaching movements in children with CP.METHOD Thirteen children (ten females, three males) with spastic hemiplegic, diplegic, or quadriplegic CP affecting at least one arm (mean age 9y, SD 1.6y; range 6-11y; Manual Ability Classification System [MACS] levels II-IV) were evaluated three time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 34 publications
0
36
1
1
Order By: Relevance
“…Schneiberg et al [12] previously reported between session reliability during a reach-to-grasp task. They found somewhat higher measurement errors for elbow and shoulder flexion (SEM b 5.3-6.38) compared to our results for RGS (SEM b 2.6-3.28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schneiberg et al [12] previously reported between session reliability during a reach-to-grasp task. They found somewhat higher measurement errors for elbow and shoulder flexion (SEM b 5.3-6.38) compared to our results for RGS (SEM b 2.6-3.28).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical implementation of the measurement procedure additionally requires the establishment of its reliability in patient groups. Schneiberg et al [12] previously reported between session reliability of endpoint spatial and kinematic parameters during reach-to-grasp objects at different distances. They reported overall moderate to excellent reliability for elbow and shoulder flexion, with measurement errors ranging from 58 to 108.…”
Section: Introductionmentioning
confidence: 99%
“…Visual observation of movement fluency is used by therapists to guide the planning and evaluation of interventions aimed at restoring movement [27]. Improving movement fluency is perceived by therapists to be associated with improvements in function [6], and has been shown to relate to energy cost [33].…”
Section: Introductionmentioning
confidence: 99%
“…Despite fundamental to this scope is the knowledge of the uncertainty about kinematics indexes measurements, very few papers [4] have actually addressed the problem of reproducibility of these indexes; perhaps because kinematics variables are task specific so that reliability should be interpreted in the context of task requirements, depending on type, amplitude and velocity of the motor task and because has not yet reached a common consensus on kinematics indexes and algorithms to use.…”
Section: Introductionmentioning
confidence: 99%